2019
DOI: 10.3390/nano9091320
|View full text |Cite
|
Sign up to set email alerts
|

Graphene−Perfluoroalkoxy Nanocomposite with High Through-Plane Thermal Conductivity Fabricated by Hot-Pressing

Abstract: With the rapid development of electronics and portable devices, polymer nanocomposites with high through-plane thermal conductivity (TC) are urgently needed. In this work, we fabricated graphene nanosheets−perfluoroalkoxy (GNs−PFA) composite sheets with high through-plane TCs via hot-pressing followed by mechanical machining. When the GNs content exceeded 10 wt%, GNs were vertically aligned in the PFA matrix, and the through-plane TCs of nanocomposites were 10–15 times higher than their in-plane TCs. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…We also found that during hydrogel molding, the surface tension and the sheet structure of composites made LmGNP tend to be horizontally distributed. Furthermore, the hot-pressing process enhanced the horizontal orientation of LmGNP, which built thermally conductive paths in the horizontal direction . It is worth noting that a large amount of Li + existing in the LiOH/urea solution will also break hydrogen bonds between LmGNPs when adding LmGNP into dissolved cellulose, making the LmGNPs uniformly distributed in the solution, which eventually gives the composite a uniform internal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that during hydrogel molding, the surface tension and the sheet structure of composites made LmGNP tend to be horizontally distributed. Furthermore, the hot-pressing process enhanced the horizontal orientation of LmGNP, which built thermally conductive paths in the horizontal direction . It is worth noting that a large amount of Li + existing in the LiOH/urea solution will also break hydrogen bonds between LmGNPs when adding LmGNP into dissolved cellulose, making the LmGNPs uniformly distributed in the solution, which eventually gives the composite a uniform internal structure.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the hot-pressing process enhanced the horizontal orientation of LmGNP, which built thermally conductive paths in the horizontal direction. 55 It is worth noting that a large amount of Li + existing in the LiOH/urea solution will also break hydrogen bonds between LmGNPs when adding LmGNP into dissolved cellulose, 56 making the LmGNPs uniformly distributed in the solution, which eventually gives the composite a uniform internal structure. This may possibly make the overall properties of the composites more stable and homogeneous.…”
Section: Chemical Composition and Microstructure Ofmentioning
confidence: 99%
“…Afterwards, the BNNs–PFA slurry was dried at 120 °C for 24 h in a vacuum oven to remove the residual ethanol. The obtained BNNs–PFA powder was put into a mold and heated at 400 °C for 1 h. The molten BNNs–PFA sample was hot-pressed at 380 °C under a pressure of 15 MPa for 15 min, then cooled to room temperature under the ambient pressure to form bulk composites [28]. The properties of these composites were then examined.…”
Section: Methodsmentioning
confidence: 99%